Specifics of the Microfinance Market Development in Russia - NIKOLAEVA, Tatiana Petrovna; PANOVAz, Tatiana Aleksandrovna; VERSHININA, Anna Aleksandrovna (Journal of Advanced Research in Law and Economics, 2020)
The specifics of the formation and development of the microfinance market in Russia as an alternative to bank lending are described in the article. The need of economic agents for financial services and the creation of an efficient financial credit system is justified. The content of relations arising in the process of microfinance and microlending is disclosed, their advantages and disadvantages are described, and the history of their occurrence is highlighted. The factors affecting the development of the microfinance market are identified, and the stages of its development in Russia are reviewed. The legal framework for the operation of microfinance organizations (microlenders) is covered, and the important role of the Bank of Russia in regulating their activities is revealed. The role of credit in the economy and its ability to fasten the process of meeting the household and personal needs are defined. It is considered as a tool for the economy regulation. The emergence of new forms and methods of lending is justified, and their influence on the socioeconomic development of society is reviewed. It is noted that microfinance is one of the fastest growing sectors of the financial market in the face of declining bank lending volumes for consumer loans. The state of the microlending market is analyzed. The strengthening of supervision over the provision of microloans is substantiated, since they are in demand by many economic agents, including the population, private entrepreneurs, and legal entities.